In Vitro Study to Evaluate the Effect of 2% Chlorhexidine Solution Application on the Microleakage of resin composite with Primary Teeth Dentine (Journal of Hama University, 2021)
With the increasing use of composite resin as a cosmetic restorative material at the level of posterior teeth, the trend of clinical and in vetro studies to research mechanical and physical properties related to composites and modern linking systems accompanying their use; increase The aim is to improve the results of the use of each of them for the better. To assess the effect of applying chlorhexidine solution 2% on the forces of bonding compost with temporary dentine, by assessing the Microleakage. The study included 40 healthy, newly extracted, primary human molars, distributed equally and randomly to two groups, group (1) restored with composite without applying chlorhexidine solution 2%, while group (2) was filled with composites with application of chlorhexidine solution 2% for 60 seconds and after acid scratching through them, the Microleakage was studied. The composite resin fillings are prepared and then kept for 6 months with distilled water. The Microleakage test was done with a stereo microscope, with a 20% magnification. an improvement in the bonding of the composite resin with primary teeth dentin when applying a 2% chlorhexidine solution after acid scratching , thus reducing Microleakage